Henoch-Schonlein Purpura in 14 years-old Boy: A Case Report - Theresia Monica Rahardjo; Chandni P. Daryanani; Apriani Lam; Maxzillion Sky Kasnadi; Nadya Ariella; Stefanie Sumartono; Syifa Navisah (Medical Clinical Update, 2023)
Henoch-Schonlein Purpura is the most common early life vasculitis in children. More than 90% arebelow ten years of age, with a median age of six years. This condition is a genetically autoinflam-matory disease. Immunoglobulin A plays an important role in the pathogenesis of his disease. It iscommonly self-restricting and harmless, but concomitant nephritis may occur as complication